2019
DOI: 10.1111/eva.12828
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic selection under two contrasting environments in wild sunflower and its crop–wild hybrid

Abstract: Hybridization is a common phenomenon in plants and can lead to the introgression of alleles from one population into another, generate new hybrid lineages, or cause species extinction. The environmental conditions and the genetic background of the participating populations may influence these outcomes since they can affect the fitness of hybrids, thereby increasing or decreasing the chances of introgression. Thus, it is important to understand the context‐dependent prospects for introgression of alleles into d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 98 publications
0
52
1
Order By: Relevance
“…This indicates that crop-wild hybridization is not required but it may facilitate the ecological transition from ruderal to agricultural habitats. Recently, we showed that wild-like traits are under selection in both ruderal and agricultural habitats, but selection is generally weaker in the latter (Presotto et al, 2019). A weaker selection for wild-like traits can explain why crop-wild hybrids are (apparently) more successful away from hybrid zones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that crop-wild hybridization is not required but it may facilitate the ecological transition from ruderal to agricultural habitats. Recently, we showed that wild-like traits are under selection in both ruderal and agricultural habitats, but selection is generally weaker in the latter (Presotto et al, 2019). A weaker selection for wild-like traits can explain why crop-wild hybrids are (apparently) more successful away from hybrid zones.…”
Section: Discussionmentioning
confidence: 99%
“…In sunflower, no major genes of large effect have been identified for seed dormancy but many small-effect QTLs (Brunick, 2007; Gandhi et al, 2005), making the evolution of seed dormancy through new mutations in multiple regions very unlikely. Hybridization between wild and cultivated sunflowers leads to high phenotypic and genetic variation on which selection can act (Muller et al, 2011; Presotto et al, 2019). After hybridization, wild and cultivated alleles starting at high frequencies and novel recombinations may produce transgresive phenotypes (Rieseberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar pattern was also detected in sunflower (Mercer et al, 2007 ), lettuce (Hartman et al, 2012 ), radish (Hegde et al, 2006 , Snow et al, 2009 ), and rape (Rose et al, 2009 ). Together, these findings suggest that some domestication traits and genome segments originating from crops may maintain and enhance crop-wild hybrid fitness (Mercer et al, 2007 ; Corbi et al, 2017 ; Presotto et al, 2019 ), although crop traits are expected to reduce fitness in wild populations (Stewart et al, 2003 ; Hails and Morley, 2005 ).…”
Section: Discussionmentioning
confidence: 99%